Peran Pemerintahan Desa dalam Menegakkan Sanksi Hukum Adat Wake Uru Sorong Tada di Desa Heo Paut Kecamatan Hewokloang Kabupaten Sikka - Alminus Arian Nong Bao (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
This study aims to examine the role of the Village Government in enforcing customary law sanctions of Wake Uru Sorong Tada and to analyze the effectiveness of its implementation in Heo Puat Village, Hewokloang District, Sikka Regency. Wake Uru Sorong Tada is a form of customary law that functions as a traditional prohibition to regulate and protect community ownership of agricultural products and commodities. This research employs a qualitative descriptive method. Data were collected through observation, in-depth interviews, and documentation involving key informants such as the village head, Village Consultative Body members, traditional leaders, and community members. Data analysis was conducted using the interactive model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that the Heo Puat Village Government plays an active role as a facilitator, mediator, and guarantor in enforcing customary sanctions in accordance with Village Regulation Number 2 of 2009. The village government does not directly determine the sanctions but collaborates closely with customary institutions in resolving violations. The enforcement of Wake Uru Sorong Tada customary law sanctions is considered effective in maintaining social order, security, and a sense of safety in property ownership among community members. The strict and binding nature of customary sanctions has significantly increased legal awareness and minimized social conflicts within the village.